Akumulacija kapitala in nestabilnost produkcije prostora v kapitalizmu - Ploštajner, Klemen (Družboslovne razprave, 2018)
The production of space in capitalism is marked by instability, as expressed in both its materiality and its use. In the article, we seek to understand this historical specificity of spatial instability in capitalism through analysis of the logic of the circuit of capital and its intertwining with the production of space. The unsuitability of spatial forms is no coincidence, but is the expression of the production of space being subordinated to the logic of capital accumulation, marked by the constant revolutionising of both the forces and relations of production. However, space and its production are not just a reaction to the circuit of capital, but permeate the whole process with the dynamic tension between fixity and mobility, the production and realisation of surplus value, the absolute and relative conception of space. The instability of spatial forms thus expresses capitalism's constant inability to solve its internal contradictions by producing space, and the contradictory demands that capitalism brings into it.
Keywords: Accumulation of capital; Akumulacija kapitala; Capitalism; Kapitalizem; Prostor; Space